Children's Moral Education towards Both Parents (Analysis of QS. Al-Isra Verse 24) - Indah Handayani; Ahmad Khotibul Umam (Konsultan Jurnal Ilmiah Indonesia, 2025)
This research aims to analyze educational interpretations of children's moral education towards parents by considering this paper as an educational interpretation assignment. The subject of this research is that a child must respect his parents because a child's own morals must be applied to both of our parents. This research concludes that morals towards parents are something that is very important. Because, parents are the people who introduce us to the world from childhood to adulthood. And every parent definitely has hopes that their child will become successful, dutiful to their parents, and become better and pious.